CATH-2 and LL-37 increase mannose receptor expression, antigen presentation and the endocytic capacity of chicken mononuclear phagocytes. (October 2017) - Kraaij, Marina D.; van Dijk, Albert; Haagsman, Henk P.
Highlights: L-CATH-2, D-CATH-2 and LL-37 increase mannose receptor expression. L-CATH-2, D-CATH-2 and LL-37 increase antigen presentation. L-CATH-2, D-CATH-2 and LL-37 increase endocytosis. L-CATH-2, D-CATH-2 and LL-37 modulate the immune response of chicken immune cells. Abstract: Cathelicidins display in vitro and in vivo immunomodulatory activities and are part of the innate immune system. Previously, we found that in ovo treatment with chicken cathelicidin CATH-2 partially protects young broilers against respiratory E. coli infection. To determine the cellular aspects of this protection, we investigated immunomodulatory effects of CATH-2 and the human cathelicidin LL-37 on primary chicken peripheral blood mononuclear cells (PBMCs). Treatment of chicken PBMCs with L-CATH-2, D-CATH-2 or LL-37 increased the percentage of mononuclear phagocytes, but decreased that of B cells. L-CATH-2, D-CATH-2 and LL-37 treatment of chicken PBMCs also enhanced the expression levels of mannose receptor MRC1 and antigen presentation markers MHCII, CD40 and CD86 on mononuclear phagocytes, indicating increased antigen presentation capacity. Concomitantly, L-CATH-2, D-CATH-2 and LL-37 neutralized LPS-induced cytokine production, while increasing the endocytic capacity. We conclude that L-CATH-2, D-CATH-2 and LL-37 can modulate the immune response of primary chicken immune cells by increasing mannose receptor expression, antigen presentation, endocytosis and neutralizing LPS-induced cytokine production and as a result augment activation of the adaptive immune system.